Comparative study of nasal mask versus nasal prong in terms of nasal septal necrosis for delivering nasal continuous positive airway pressure in newborns with respiratory distress - Solanki, Jayesh Ratilal; Bhil, Dipika L (Indian Journal of Child Health, 2019)
Background: Respiratory distress syndrome (RDS) requires management by oxygen therapy and mechanical ventilation. Continuous positive airway pressure (CPAP) being simple, cost-effective, and non-invasive respiratory support is used to prevent airway injury as well as the development of bronchopulmonary dysplasia. Objectives: The study was to describe the comparison of nasal septum necrosis and to categorize severity of nasal septum trauma while using nasal prongs and nasal masks for nasal CPAP (nCPAP) in neonates with RD. Materials and Methods: A prospective randomized controlled study was carried out in 200 neonates admitted in neonatal intensive care unit and these neonates were randomized to receive either nasal mask or nasal prong as an interface for nCPAP. Complete blood count, C-reactive protein, blood culture, and chest X-ray were done. All infants were observed for 72 h for the development of nasal septal necrosis in each interface. All variables were analyzed with the help of Chi-square test. Results: Of the total 200 neonates included in the study, 9% neonates of prong group developed nasal septum necrosis, while no incidence of septum necrosis noted in mask group. Conclusion: Nasal masks were comparatively better than nasal prongs as nasal septum trauma occurred only in neonates with nasal prongs group.